2010
DOI: 10.1086/653945
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Outbreak of Foodborne Botulism Linked to Contaminated Sausage in Hebei Province, China

Abstract: In 2007, an outbreak of foodborne botulism occurred in Hebei province, China. An epidemiological investigation and laboratory detection studies showed that sausage contaminated by type A Clostridium botulinum caused this outbreak of food poisoning. Its clinical and epidemiological features were different from previous reports of food poisoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…However, the range is wide and botulism may affects any age groups from neonatal to elderly. Some authors reported slightly higher incidence of FBB in rural areas [5,7,19,27,28]. In our study, 56.1% of patients were residents of urban areas, but, this may still consistent with the results of other studies because according to the last national census, more than 62.7% of our province's inhabitants live in urban areas.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the range is wide and botulism may affects any age groups from neonatal to elderly. Some authors reported slightly higher incidence of FBB in rural areas [5,7,19,27,28]. In our study, 56.1% of patients were residents of urban areas, but, this may still consistent with the results of other studies because according to the last national census, more than 62.7% of our province's inhabitants live in urban areas.…”
Section: Discussionsupporting
confidence: 92%
“…C. botulinum is an anaerobic, gram-positive, spore-forming bacillus [5]. Its hardy spores are ubiquitously spread in soil and aquatic sediments and commonly contaminate foods [2,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with traditional MLA or ELISA methods, the assay takes only half a day and consumes significantly less sample and reagents, which will significantly reduce assay cost and simplify disposal. In China, the majority of the cases caused by botulism were from less-developed rural areas [26]. This assay may contribute to the improvement of treatment for botulism without any requirements for skilled laboratory staff, additional facilities, or equipments.…”
Section: Discussionmentioning
confidence: 99%
“…10 First, a colloidal gold solution was prepared by constant mixing of 0.01% (w/v) chloroauric acid hydrate (gold chloride) and 0.01% (w/v) sodium citrate for about 10 min at boiling temperature. The pH of the solution was then titrated to 8.5 with K 2 CO 3 .…”
Section: Laboratory Investigationmentioning
confidence: 99%